Objective and subjective factors of efficiency and performance of medical audit - V. S. Biryukov (Kazimierz Wielki University, 2017)
The work is devoted to analysis factors affecting the effective operation of quality management systems in health care institutions. It is shown important role of quality of carrying out audits, internal and external, in elimination of various kinds of risks and discrepancies in activity of medical institutions. Two main factors were revealed which influencing the quality of audit: 1. Subjective or "human" factor, consisting in sufficient motivation of the top management and internal auditors of medical institutions. 2. Objective or technological factor, consisting in sufficient training of internal auditors, adequacy selected audit methodology, etc.